SiC-coated SiO2 nanofiber aerogel and preparation method thereof
By preparing SiC@SiO2 nanofiber aerogel in electromagnetic wave absorption materials, the shortcomings in the existing materials in oxidation resistance, dispersion and temperature dependence are solved, and the material preparation with high thermal stability and impedance matching characteristics is achieved, expanding its application prospects in electromagnetic wave absorption and heat insulation.
Patent Information
- Application Number
- CN202411759304.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-04
AI Technical Summary
The existing magnetic loss and conduction loss materials have problems with oxidation resistance, dispersion and temperature dependence in electromagnetic wave absorption, which limits their practical application.
By mixing the carbon source and the silicon source, drying and grinding, a precursor powder was obtained, and then sintered and oxidized under an argon atmosphere to prepare SiC@SiO2 nanofiber aerogel.
This method reduces the synthesis temperature and time of SiC@SiO2 nanofiber aerogel, improves its thermal stability and impedance matching characteristics, and gives it potential electromagnetic wave absorption and thermal insulation material application prospects.
Smart Images

Figure CN119551677A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aerogels, and in particular to a SiC@SiO2 nanofiber aerogel and a preparation method thereof. Background Art
[0002] With the widespread application of electromagnetic wave technology, people are paying more and more attention to electromagnetic wave pollution. Using electromagnetic wave absorption technology to reduce electromagnetic wave pollution is a common method at present. Electromagnetic wave absorption technology requires efficient and multifunctional electromagnetic wave absorption materials. Generally speaking, dielectric loss, magnetic loss and conduction loss are the main factors of electromagnetic wave energy consumption, and are considered to be the main electromagnetic wave absorption mechanisms at present. Due to their excellent microwave absorption performance, magnetic loss materials have been widely used in electromagnetic wave absorption. Common magnetic loss materials include Fe, Co, Ni, ferrite and magnetic oxides. However, magnetic loss materials usually have poor oxidation resistance and dispersibility, and high density, which greatly limits the practical application of magnetic loss materials. Although conductive loss materials also show efficient electromagnetic wave absorption performance, such as carbon-based materials and conductive polymers, they can only work within a certain temperature range. Therefore, the research on dielectric loss materials has received more and more attention.
[0003] Dielectric loss is usually caused by conduction loss, interface polarization and defect polarization, and also includes dipole / molecular polarization, electronic polarization, ionic polarization and atomic polarization. Typical dielectric loss materials are carbides, non-magnetic oxides and sulfides, including but not limited to SiC, MXene, ZnO, MnO2, MoS2 and CuS. Among these materials, SiC-based materials have excellent thermal and chemical stability and are expected to become a popular material for high-temperature electromagnetic wave absorption in the future.
[0004] Therefore, the development of SiC-based dielectric loss materials with excellent performance has broad application prospects. Summary of the invention
[0005] The purpose of the present invention is to provide a SiC@SiO2 nanofiber aerogel and a preparation method thereof in view of the deficiencies in the prior art.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing SiC@SiO2 nanofiber aerogel, comprising the following steps:
[0008] (1) mixing a carbon source and a silicon source, drying and grinding them in sequence to obtain a precursor powder;
[0009] (2) sintering the precursor powder under an argon atmosphere to obtain SiC nanofiber aerogel;
[0010] (3) Oxidizing the SiC nanofiber aerogel to obtain SiC@SiO2 nanofiber aerogel.
[0011] Preferably, the carbon source in step (1) comprises one or more of wheat flour, corn flour and sorghum flour;
[0012] The silicon source is silica sol mixed with nano silicon dioxide and water, and the mass content of nano silicon dioxide in the silicon source is 20-40%.
[0013] Preferably, the mass ratio of the carbon source to the silicon source in step (1) is 2-4.5:33.33.
[0014] Preferably, the drying temperature in step (1) is 60 to 100° C., and the drying time is 10 to 30 hours.
[0015] Preferably, the particle size of the precursor powder in step (1) is 1 to 50 μm.
[0016] Preferably, the sintering temperature in step (2) is 1300-1600° C., the sintering time is 1-5 h, the heating rate to the sintering temperature is 3-15° C. / min; and the flow rate of the argon gas is 5-300 mL / min.
[0017] Preferably, the oxidation in step (3) is carried out in an air atmosphere, the oxidation temperature is 1000-1200°C, the oxidation time is 0.5-5h, and the heating rate to the oxidation temperature is 5-10°C / min.
[0018] Preferably, stirring is performed during the mixing process in step (1), the stirring speed is 30 to 105 r / min, and the stirring time is 2 to 4 h.
[0019] The invention also provides SiC@SiO2 nanofiber aerogel prepared by the preparation method.
[0020] The beneficial effects of the present invention include the following:
[0021] 1) The present invention uses wheat flour, corn flour and sorghum flour as carbon sources, which are low-cost and more environmentally friendly, and the degree of environmental pollution caused by the production and processing processes is extremely small; on the other hand, the residual carbon source can be decomposed at a relatively low temperature to obtain SiC nanofiber aerogel with higher purity, thereby ensuring the high purity of SiC@SiO2 nanofiber aerogel.
[0022] 2) The present invention prepares SiC@SiO2 nanofiber aerogel by chemical vapor deposition under argon atmosphere, which not only significantly reduces the synthesis temperature of SiC@SiO2 nanofiber aerogel, but also shortens the time required for synthesis and reduces energy consumption; the preparation method is simple, environmentally friendly and efficient.
[0023] 3) In the present invention, SiC nanofiber aerogel with a small diameter and a high aspect ratio is obtained by in-situ radial growth, and then SiC@SiO2 nanofiber aerogel with a core-shell structure and a high aspect ratio is obtained by oxidation. The aerogel has high thermal stability and impedance matching characteristics, can be used as a potential electromagnetic wave absorption material and thermal insulation material, and has many application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope image of the SiC@SiO2 nanofiber aerogel prepared in Example 1, with a scale of 30 μm;
[0025] Figure 2 This is a scanning electron microscope image of the SiC@SiO2 nanofiber aerogel prepared in Example 1, with a scale of 400 μm;
[0026] Figure 3 This is the X-ray diffraction pattern of the SiC@SiO2 nanofiber aerogel prepared in Example 1. DETAILED DESCRIPTION
[0027] The present invention provides a method for preparing SiC@SiO2 nanofiber aerogel, comprising the following steps:
[0028] (1) mixing a carbon source and a silicon source, drying and grinding them in sequence to obtain a precursor powder;
[0029] (2) sintering the precursor powder under an argon atmosphere to obtain SiC nanofiber aerogel;
[0030] (3) Oxidizing the SiC nanofiber aerogel to obtain SiC@SiO2 nanofiber aerogel.
[0031] In the present invention, the carbon source in step (1) preferably comprises one or more of wheat flour, corn flour and sorghum flour;
[0032] The silicon source is preferably a silica sol formed by mixing nano-silicon dioxide and water. The mass content of nano-silicon dioxide in the silicon source is preferably 20-40%, more preferably 25-35%, and more preferably 30%.
[0033] In the present invention, the mass ratio of the carbon source to the silicon source in step (1) is preferably 2-4.5:33.33, more preferably 2.5-4.2855:33.33, and even more preferably 2.857-3.428:33.33.
[0034] In the present invention, the drying temperature in step (1) is preferably 60-100°C, more preferably 70-90°C, and more preferably 80°C; the drying time is preferably 10-30h, more preferably 12-24h, and more preferably 18h.
[0035] In the present invention, the particle size of the precursor powder in step (1) is preferably 1 to 50 μm, more preferably 10 to 40 μm, and even more preferably 20 to 30 μm.
[0036] In the present invention, in step (2), the precursor powder is preferably placed in a vacuum environment first, and then argon gas is introduced to start heating for sintering; the vacuum degree of the vacuum environment is preferably -0.2 to -0.1 MPa, and more preferably -0.15 MPa.
[0037] In the present invention, the sintering temperature in step (2) is preferably 1300-1600°C, more preferably 1400-1500°C, and more preferably 1450°C; the sintering time is preferably 1-5h, more preferably 2-4h, and more preferably 3h; the heating rate to the sintering temperature is preferably 3-15°C / min, and more preferably 5-10°C / min; the flow rate of the argon gas is preferably 5-300mL / min, more preferably 50-250mL / min, and more preferably 100-200mL / min.
[0038] In the present invention, the sintering in step (2) is preferably first heated to an intermediate temperature at a first heating rate, and then heated to a sintering temperature at a second heating rate; the first heating rate is different from the second heating rate; the intermediate temperature is preferably 800-1000°C, and more preferably 900°C.
[0039] In the present invention, after the sintering in step (2) is completed, the temperature is preferably naturally lowered to room temperature to obtain SiC nanofiber aerogel.
[0040] In the present invention, the SiC nanofiber aerogel in step (2) is preferably deposited on the lid of the container containing the precursor powder, and the lid is separated from the precursor powder, which can make the deposited SiC nanofiber aerogel have a higher purity, thereby ensuring the high purity of the SiC@SiO2 nanofiber aerogel.
[0041] In the present invention, the oxidation in step (3) is preferably carried out in an air atmosphere, and the oxidation temperature is preferably 1000-1200°C, more preferably 1050-1150°C, and more preferably 1100°C; the oxidation time is preferably 0.5-5h, more preferably 1-4h, and more preferably 2-3h; the heating rate to the oxidation temperature is preferably 5-10°C / min, more preferably 7-9°C / min, and more preferably 8°C / min.
[0042] In the present invention, after the oxidation in step (3) is completed, the temperature is preferably naturally lowered to room temperature to obtain SiC@SiO2 nanofiber aerogel.
[0043] In the present invention, stirring is preferably performed during the mixing process in step (1), and the stirring speed is preferably 30 to 105 r / min, more preferably 50 to 90 r / min, and more preferably 60 to 80 r / min; the stirring time is preferably 2 to 4 h, more preferably 2.5 to 3.5 h, and more preferably 3 h.
[0044] The invention also provides SiC@SiO2 nanofiber aerogel prepared by the preparation method.
[0045] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0046] Example 1
[0047] 4.2855g wheat flour and 33.33g silica sol (the mass content of nano-silicon dioxide in the silica sol is 30%) are placed in a beaker, and a 2.5cm polytetrafluoroethylene rotor is used to magnetically stir at a speed of 90r / min for 2h to obtain a carbon-silicon mixture. The carbon-silicon mixture is placed at 100°C and dried for 12h, and then ground to obtain a precursor powder with a particle size of 50μm.
[0048] The precursor powder was placed in a graphite crucible of 30mm×40mm×70mm in size, covered with a lid and placed in a vacuum atmosphere tube furnace with a vacuum degree of -0.1MPa. Argon was introduced into the vacuum atmosphere tube furnace at a flow rate of 200mL / min, and the vacuum atmosphere tube furnace was heated to 800℃ at a rate of 10℃ / min, and then heated to 1500℃ at a rate of 5℃ / min, and sintered at 1500℃ for 5h. After the insulation was completed, the temperature naturally dropped to room temperature with the furnace, and the product deposited on the graphite crucible lid was SiC nanofiber aerogel.
[0049] The SiC nanofiber aerogel was placed in a muffle furnace, and the temperature was raised to 1100°C at a rate of 5°C / min in an air atmosphere, and the temperature was kept at 1100°C for 0.5h for oxidation. After the temperature was kept at room temperature, the temperature naturally dropped to room temperature, and the SiC@SiO2 nanofiber aerogel was obtained.
[0050] The SiC@SiO2 nanofiber aerogel prepared in this example is marked as SiC@SiO2 NFA.
[0051] The microstructure of the SiC@SiO2 nanofiber aerogel prepared in Example 1 was observed using a scanning electron microscope EVO MA 15 / LS15 produced by the German ZEISS company. Figure 1 This is a scanning electron microscope image of the SiC@SiO2 nanofiber aerogel prepared in Example 1, with a scale of 30 μm. Figure 2 This is a scanning electron microscope image of the SiC@SiO2 nanofiber aerogel prepared in Example 1, with a scale of 400 μm. Figure 1 , 2 It can be seen that the SiC@SiO2 nanofiber aerogel has a high aspect ratio and a linear structure.
[0052] The crystal structure of the SiC@SiO2 nanofiber aerogel prepared in Example 1 was characterized by using an X-ray powder diffractometer Smart Lab produced by Rigaku Corporation of Japan. Figure 3 This is the X-ray diffraction pattern of the SiC@SiO2 nanofiber aerogel prepared in Example 1.
[0053] Example 2
[0054] 2.857g corn flour and 33.33g silica sol (the mass content of nano-silicon dioxide in the silica sol is 40%) are placed in a beaker, and a 2.5cm polytetrafluoroethylene rotor is used to magnetically stir at a speed of 90r / min for 2h to obtain a carbon-silicon mixture. The carbon-silicon mixture is placed at 100°C and dried for 12h, and then ground to obtain a precursor powder with a particle size of 30μm.
[0055] The precursor powder was placed in a graphite crucible of 30mm×40mm×70mm in size, covered with a lid and placed in a vacuum atmosphere tube furnace with a vacuum degree of -0.1MPa. Argon was introduced into the vacuum atmosphere tube furnace at a flow rate of 200mL / min, and the vacuum atmosphere tube furnace was heated to 1000℃ at a rate of 10℃ / min, and then heated to 1500℃ at a rate of 5℃ / min, and sintered at 1500℃ for 5h. After the insulation was completed, the temperature naturally dropped to room temperature with the furnace, and the product deposited on the graphite crucible lid was SiC nanofiber aerogel.
[0056] The SiC nanofiber aerogel was placed in a muffle furnace, and the temperature was raised to 300°C at a rate of 5°C / min in an air atmosphere, and then raised to 1050°C at a rate of 10°C / min, and then kept at 1050°C for 2 hours for oxidation. After the insulation, the temperature naturally dropped to room temperature with the furnace, and the SiC@SiO2 nanofiber aerogel was obtained.
[0057] Example 3
[0058] 3.428g of sorghum flour and 33.33g of silica sol (the mass content of nano-silicon dioxide in the silica sol is 20%) were placed in a beaker, and a 2.5cm polytetrafluoroethylene rotor was used to magnetically stir at a speed of 90r / min for 2h to obtain a carbon-silicon mixture. The carbon-silicon mixture was dried at 100°C for 12h, and then ground to obtain a precursor powder with a particle size of 10μm.
[0059] The precursor powder was placed in a graphite crucible of 30mm×40mm×70mm in size, covered with a lid and placed in a vacuum atmosphere tube furnace with a vacuum degree of -0.1MPa. Argon was introduced into the vacuum atmosphere tube furnace at a flow rate of 200mL / min, and the vacuum atmosphere tube furnace was heated to 1000℃ at a rate of 10℃ / min, and then heated to 1500℃ at a rate of 5℃ / min, and sintered at 1500℃ for 5h. After the insulation was completed, the temperature naturally dropped to room temperature with the furnace, and the product deposited on the graphite crucible lid was SiC nanofiber aerogel.
[0060] The SiC nanofiber aerogel was placed in a muffle furnace, and the temperature was raised to 300°C at a rate of 5°C / min in an air atmosphere, and then raised to 1200°C at a rate of 5°C / min, and then kept at 1200°C for 1 hour for oxidation. After the insulation was completed, the temperature naturally dropped to room temperature with the furnace, and the SiC@SiO2 nanofiber aerogel was obtained.
[0061] Example 4
[0062] 2.5g wheat flour and 33.33g silica sol (the mass content of nano-silicon dioxide in the silica sol is 25%) are placed in a beaker, and a 2.5cm polytetrafluoroethylene rotor is used to magnetically stir at a speed of 50r / min for 4h to obtain a carbon-silicon mixture. The carbon-silicon mixture is placed at 80°C and dried for 18h, and then ground to obtain a precursor powder with a particle size of 20μm.
[0063] The precursor powder was placed in a graphite crucible of 30mm×40mm×70mm in size, covered with a lid and placed in a vacuum atmosphere tube furnace with a vacuum degree of -0.2MPa. Argon was introduced into the vacuum atmosphere tube furnace at a flow rate of 50mL / min, and the vacuum atmosphere tube furnace was heated to 800℃ at a rate of 15℃ / min, and then heated to 1300℃ at a rate of 5℃ / min, and sintered at 1300℃ for 3h. After the insulation was completed, the temperature naturally dropped to room temperature with the furnace, and the product deposited on the graphite crucible lid was SiC nanofiber aerogel.
[0064] The SiC nanofiber aerogel was placed in a muffle furnace, and the temperature was raised to 1100°C at a rate of 8°C / min in an air atmosphere, and the temperature was kept at 1100°C for 3 hours for oxidation. After the temperature was kept at room temperature, the temperature naturally dropped to room temperature, and the SiC@SiO2 nanofiber aerogel was obtained.
[0065] Example 5
[0066] 2g wheat flour and 33.33g silica sol (the mass content of nano-silicon dioxide in the silica sol is 35%) are placed in a beaker, and a 2.5cm polytetrafluoroethylene rotor is used to magnetically stir at a speed of 70r / min for 4h to obtain a carbon-silicon mixture. The carbon-silicon mixture is placed at 60°C and dried for 30h, and then ground to obtain a precursor powder with a particle size of 30μm.
[0067] The precursor powder was placed in a graphite crucible of 30mm×40mm×70mm in size, covered with a lid and placed in a vacuum atmosphere tube furnace with a vacuum degree of -0.1MPa. Argon was introduced into the vacuum atmosphere tube furnace at a flow rate of 300mL / min, and the vacuum atmosphere tube furnace was heated to 800℃ at a rate of 10℃ / min, and then heated to 1400℃ at a rate of 3℃ / min, and sintered at 1400℃ for 2h. After the insulation was completed, the temperature naturally dropped to room temperature with the furnace, and the product deposited on the lid of the graphite crucible was SiC nanofiber aerogel.
[0068] The SiC nanofiber aerogel was placed in a muffle furnace, and the temperature was raised to 1000°C at a rate of 10°C / min in an air atmosphere, and the temperature was kept at 1000°C for 4 hours for oxidation. After the temperature was kept at room temperature, the temperature naturally dropped to room temperature, and the SiC@SiO2 nanofiber aerogel was obtained.
[0069] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing SiC@SiO2 nanofiber aerogel, characterized in that: The following steps are included: (1) mixing a carbon source and a silicon source, drying and grinding them in sequence to obtain a precursor powder; (2) sintering the precursor powder under an argon atmosphere to obtain SiC nanofiber aerogel; (3) Oxidizing the SiC nanofiber aerogel to obtain SiC@SiO2 nanofiber aerogel.
2. The preparation method according to claim 1, characterized in that: The carbon source in step (1) comprises one or more of wheat flour, corn flour and sorghum flour; The silicon source is a silica sol formed by mixing nano silicon dioxide and water, and the mass content of the nano silicon dioxide in the silicon source is 20-40%.
3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the carbon source to the silicon source in step (1) is 2-4.5:33.
33.
4. The preparation method according to claim 3, characterized in that: The drying temperature in step (1) is 60 to 100° C., and the drying time is 10 to 30 hours.
5. The preparation method according to claim 4, characterized in that: The particle size of the precursor powder in step (1) is 1 to 50 μm.
6. The preparation method according to claim 4 or 5, characterized in that: In step (2), the sintering temperature is 1300-1600° C., the sintering time is 1-5 hours, the heating rate to the sintering temperature is 3-15° C. / min; the flow rate of the argon gas is 5-300 mL / min.
7. The preparation method according to claim 6, characterized in that: The oxidation in step (3) is carried out in an air atmosphere, the oxidation temperature is 1000-1200° C., the oxidation time is 0.5-5 h, and the heating rate to the oxidation temperature is 5-10° C. / min.
8. The preparation method according to claim 7, characterized in that: During the mixing process of step (1), stirring is performed at a speed of 30 to 105 r / min and a stirring time of 2 to 4 h.
9. SiC@SiO2 nanofiber aerogel prepared by the preparation method according to any one of claims 1 to 8.